Subject teachers’ perceptions of academic mentoring and counseling services - Sutirna, Sutirna (COUNS-EDU: The International Journal of Counseling and Education, 2019)
In developing students’ potential requires, among others, psycho-education services. This effort can be provided not only by counselor but also by subject teachers at school. This research is aimed at investigating subject teachers’ perceptions of academic guidance and counseling services provided by the teachers to students who had learning difficulties. Employing descriptive method, this research involved fifty counseling and guidance teachers to participate as research participants. To collect data, paper- and online-based questionnaires were used. The data gathered were then categorized and analyzed. The results indicated that the majority of the subject teachers have sufficient understanding on their roles in substantially providing academic guidance and counseling related to the students’ academic problems. In addition, it was found that the counseling teachers always give the students referral to their respective teachers whenever the students get learning difficulties.